Continuous flow asymmetric synthesis of chiral active pharmaceutical ingredients and their advanced intermediates. Issue 17 (12th August 2021) - Ötvös, Sándor B.; Kappe, C. Oliver
Abstract : This review surveys continuous flow approaches for the synthesis of chiral APIs and their advanced stereogenic intermediates, covering the utilization of biocatalysis, organometallic catalysis and metal-free organocatalysis to introduce asymmetry. Abstract : Catalytic enantioselective transformations provide well-established and direct access to stereogenic synthons that are broadly distributed among active pharmaceutical ingredients (APIs). These reactions have been demonstrated to benefit considerably from the merits of continuous processing and microreactor technology. Over the past few years, continuous flow enantioselective catalysis has grown into a mature field and has found diverse applications in asymmetric synthesis of pharmaceutically active substances. The present review therefore surveys flow chemistry-based approaches for the synthesis of chiral APIs and their advanced stereogenic intermediates, covering the utilization of biocatalysis, organometallic catalysis and metal-free organocatalysis to introduce asymmetry in continuously operated systems. Single-step processes, interrupted multistep flow syntheses, combined batch/flow processes and uninterrupted one-flow syntheses are discussed herein.